2017
DOI: 10.1002/chem.201704695
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid‐Catalyzed Intramolecular [3+2] Cross‐Cycloaddition of Aziridine 2,2‐Diesters with Conjugated Dienes for Construction of Aza‐[n.2.1] Skeletons

Abstract: A novel Lewis acid-catalyzed [3+2] intramolecular cross-cycloaddition (IMCC) between aziridine 2,2-diesters and conjugated dienes has been developed. This is the first regiospecific IMCC of intramolecular 1,3-dipolar cycloadditions of azomethine ylides with carbon=carbon double bonds, and supplies a general and efficient strategy for construction of structurally complex and diverse aza-[n.2.1] skeletons. The [3+2]IMCC could be carried out under mild conditions and in gram scale. More importantly, 3-alkyl-subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 108 publications
0
2
0
1
Order By: Relevance
“…50 Similarly, appropri-ately substituted aziridines can serve as precursors to azomethine ylides, which can then participate in [3+2] cycloadditions. Wang 51 showed that tosylaziridine 166 (Scheme 32), in which the dipolarophile is part of a conjugated diene, underwent a regioselective intramolecular cycloaddition to give the bridged 7-azabicyclo[4.2.1]nonane system 167 (as opposed to the fused system) upon exposure to a substoichiometric amount of SnCl 4 .…”
Section: Cycloadditionsmentioning
confidence: 99%
“…50 Similarly, appropri-ately substituted aziridines can serve as precursors to azomethine ylides, which can then participate in [3+2] cycloadditions. Wang 51 showed that tosylaziridine 166 (Scheme 32), in which the dipolarophile is part of a conjugated diene, underwent a regioselective intramolecular cycloaddition to give the bridged 7-azabicyclo[4.2.1]nonane system 167 (as opposed to the fused system) upon exposure to a substoichiometric amount of SnCl 4 .…”
Section: Cycloadditionsmentioning
confidence: 99%
“…第二种方式为分子内 Mannich 反应(C) [55] 形成 C(4)-C(5)键. 第三种方式为同 时形成 C(3)-C(4)及 C(1)-C(8)键, 例如新颖的氮丙 啶 -共 轭 二 烯 化 合 物 分 子 内 [3 + 2] 交 叉 环 加 成 反 应 (D) [56] . 第四种方式为 C(5)-N 键的形成, 由于处于桥环 连接处, 并且涉及碳杂原子键的形成, 合成策略较多.…”
Section: 生源合成假说unclassified
“…In continuation of our ongoing research into the reactivity of substituted azabicycloheptenes, in the present work we studied the bromination and chlorination of 2‐(arylsulfonylaza)‐3‐(polychloromethyl)bicyclo[ 2.2.1 ]hept‐5‐enes 9 , 10 a – c synthesized by the reaction of highly electrophilic polychloroaldimines 7 , 8 a – c with cyclopentadiene (Table 1). Our endeavors were motivated by the fact that further substitution or elimination of halogen atoms involving the expected halogenation products open new avenues for the synthesis of functionalized azanorbornanes, azanorbornenes and their derivatives, the analogs of which are valuable reagents and promising biologically active substances [41–44] . For the first time, the features of bromination of 2‐azanorbornenes were demonstrated by Raasch [45] .…”
Section: Introductionmentioning
confidence: 99%
“…Our endeavors were motivated by the fact that further substitution or elimination of halogen atoms involving the expected halogenation products open new avenues for the synthesis of functionalized azanorbornanes, azanorbornenes and their derivatives, the analogs of which are valuable reagents and promising biologically active substances. [41][42][43][44] For the first time, the features of bromination of 2-azanorbornenes were demonstrated by Raasch. [45] In this pioneering work, 2-(arylsulfonylaza)bicyclo[2.2.1]hept-5-enes were represented by only two examples -cycloadducts derived from tosylchloralimine and tosylimine of glyoxylic acid.…”
Section: Introductionmentioning
confidence: 99%